Grip strength in healthy caucasian adults: reference values - Günther, Christian M; Bürger, Alexander; Rickert, Markus; Crispin, Alexander; Schulz, Christoph U (The Journal of hand surgery (American ed.), 2008)
The aim of this study was to update reference data of handgrip strength for healthy adults of both genders spanning a wide age range and to analyze possible factors of influence. Intraindividual and interindividual variations of grip strength and their relation to several anthropometric factors were analyzed in a standardized manner for 769 healthy adults (women, n = 403; men, n = 366) aged between 20 years and 95 years. Measurements were done in neutral position of arm, forearm, and wrist on setting II of a Baseline digital hydraulic dynamometer (NexGen Ergonomics Inc. Quebec, Canada). Mean strength was about 41% less in women (right 29 kg; left 27 kg) than in men (right 49 kg; left 47 kg) resulting in a ratio of left to right hand slightly above .95 in both genders. During the course of life, hand strength develops comparably in both genders peaking at 35 years of age and decreasing continuously further on. Anthropometric variables such as forearm circumference and length, hand size, or body mass showed a positive correlation with grip strength. Body mass index, type of work, and hand dominance showed only a partial positive correlation or no correlation with grip strength. Gender and age, followed by parameters representing body length and obesity, were observed to have the highest predictive value for handgrip strength and were therefore entered into the generation of prediction equations. We recommend side adjustment of measured values for intraindividual comparison and inclusion of information regarding anthropometric characteristics, as well as using gender- and age-adjusted reference values, whereas hand dominance can be neglected. The regression equations we generated might prove to be useful for clinicians or for those who use normative values within software to provide more accurate predictions of strength scores for specific applications.